BRITISH DRAMA IN THE EIGHTEEN THIRTIES - Morrison, Margaret M. (My University, 1970)
This study examines the most successful plays of the eighteen thirties in conjunction with contemporary commentaries on the intentions of the authors, and the reactions of critics and of audiences, in order to determine the nature of eighteen thirties drama, and thus to suggest a means of approaching the plays which will enable their particular achievement to be appreciated.
Keywords: English Language and Literature; English Language and Literature